STRATEGI MENGEMBANGKAN PERUSAHAAN MELALUI MERGER DAN AKUISISI - Shinji Putri Rahmawati; Aliza Meidana Putri; Hisan Tsabit; Nelly Hikmahtul Hoeriah; Kunto Ajibroto; Linna Ismawati (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2023)
Mergers and acquisitions are processes carried out by companies to combine the two companies with the aim of expanding market share, increasing profits generated, improving company performance and can be used as a strategy in developing a business. This study aims to find out what strategies companies should implement in developing their business through Mergers and Acquisitions. By using the literature study method and using secondary data through journals, theses, news and so on. The results of this study explain that a mature strategy is needed in the Merger and Acquisition process to achieve success. Analyzing and selecting suitable target companies, carrying out a due diligence process, reducing premium levels, integrating operations effectively and maintaining or increasing owned resources are some of the strategies needed in a successful merger or acquisition.